VISUAL PHOTOGRAPHIC COMPOSITION WITH A DESIGN APPROACH IN VERONICA SAVER'S WORK - Martinus Eko Prasetyo (Titik Imaji, 2023)
The progress of the world of photography in Indonesia has not only made photography a hobby, even photography has become a hobby that can produce both commercially and with prestige. Producing photographic works is not enough just to take a photo framing of an object in a sense (feeling), but an appropriate method is needed so that photography enthusiasts can practice it. This research focuses on the analysis of photographic composition through the study of composition according to "Brenda Tharp" in his book entitled Expressive Nature Photography, but what is interesting is that this research also examines the design composition. The development of photography in Indonesia, especially the works of a female photographer named Veronica Saver, really inspires novice photographers with her beautiful works to document many photos that have won prestigious awards. As one of the representatives of Indonesian photographers, Veronica Saver has succeeded in becoming one of the winners of GPA International Salon Photo 2021. This research will be carried out in a qualitative descriptive manner from several of Veronica Saver's photography works that have been published in GPA International Salon Photo 2021, the author wants to analyze to what extent the role of visual composition in photography as well as in visual design composition. It takes a study that can analyze this directly, which is expected to be a learning reference for beginner photographers in Indonesia.